Optimisation and improvement of police officers’ special rank types - Ye. I. Harkavtsev; M. O. Koteliukh (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the process of reforming the law enforcement system in Ukraine, in particular the creation of the National Police in 2015, and its impact on the rank system of police officers. Special attention is paid to the main changes that occurred as a result of this reform. In particular, such positive aspects as bringing police standards closer to the European level, as well as creating a new police uniform and changing the rank system are highlighted. It is important to note that the reform is aimed at improving the efficiency of law enforcement agencies and their interaction with the public. The article also highlights the problem of the lack of additional ranks and limited career opportunities for junior police officers, which can lead to professional burnout and reduced staff motivation.